Iron-nitrogen co-doped carbon-supported platinum catalyst as well as preparation method and application thereof
By introducing iron-nitrogen bonds on the surface of carbon materials as the nucleation site of platinum nanoparticles, the problem of insufficient binding strength between platinum nanoparticles and carbon support is solved, the high activity and stability of the catalyst are achieved, and the oxygen reduction performance is improved. Cyclic stability.
Patent Information
- Application Number
- CN202411355996.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-03
AI Technical Summary
In the oxygen reduction reaction of existing catalysts, the binding strength of platinum nanoparticles to carbon support is limited, resulting in particles aggregation and shedding during long-term use, attenuation of activity, and the carbon support is prone to corrosion, affecting the stability and performance of the catalyst.
By introducing iron and nitrogen atoms on the surface of carbon materials, it forms iron-nitrogen-carbon bonds as the nucleation site of platinum nanoparticles, it promotes the uniform distribution and small-size growth of platinum nanoparticles, forming single-crystal nanoparticles, and passing through iron- Nitrogen bond anchoring and graphitization improve the stability of platinum particles and the corrosion resistance of carbon support.
It significantly improves the activity and stability of the catalyst, inhibits the dissolution and agglomeration of platinum particles, enhances the corrosion resistance of the carbon support, and improves the oxygen reduction performance and cycle stability.
Smart Images

Figure CN119252950A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to an iron-nitrogen co-doped carbon-supported platinum catalyst and a preparation method and application thereof. Background Art
[0002] The oxygen reduction reaction (ORR), as the cathode reaction of proton exchange membrane fuel cells, directly affects the efficiency and power density of the cell. However, the reduction kinetics of oxygen molecules are slow, and efficient catalysts are required to accelerate the reaction process. The most efficient commercial electrocatalyst for the oxygen reduction reaction in proton exchange membrane fuel cells is a catalyst made of platinum nanoparticles dispersed on a carbon black substrate.
[0003] Many methods for preparing such catalysts have been disclosed in the prior art, for example:
[0004] Chinese patent CN 117913298 A prepares a honeycomb carbon-supported platinum catalyst. However, the high temperature and acid etching process may cause partial structural damage and pore collapse of the carbon carrier, affecting the porous properties of the final catalyst. In addition, the bonding strength between the Pt nanoparticles and the carbon carrier is limited. During long-term use, particles may agglomerate or fall off, reducing the catalytic performance.
[0005] Chinese patent CN 117282977A uses sodium citrate and sodium hydroxide to prepare porous carbon, and then uses a microwave method to load platinum to prepare a porous carbon-supported platinum catalyst, in an effort to increase active sites and evenly disperse platinum particles. However, platinum atoms without heteroatom anchoring will inevitably aggregate in long-term cycles, and since carbon carriers without graphite phases are prone to corrosion, the oxygen reduction performance of the catalyst is greatly reduced, and the stability of this type of catalyst cannot be guaranteed.
[0006] Chinese patent CN 116581316A prepared a Zn-CoZIF porous carbon-nitrogen-doped platinum-supported catalyst, and used single-atom cobalt to isolate platinum particles in an attempt to make the platinum particles as evenly dispersed as possible. However, it is difficult to form an effective platinum-cobalt coupling. After a long period of circulation, the platinum will also decouple from the cobalt and slowly mature.
[0007] Chinese patent CN 116885220 A prepared a metal iron porphyrin-derived carbon-based noble metal Pt oxygen reduction catalyst. Although the PtNP-FeSAC@MCHS catalyst provided by this invention does adopt some novel design strategies, such as using the spatial isolation effect of mesoporous carbon spheres and the strong interaction between Pt and Fe to limit the aggregation of Pt nanoparticles, the hollow carbon spheres containing Fe single atoms prepared by SiO2 hard template method and carbonization process must have certain difficulties in controlling their structure and composition, which is likely to lead to heterogeneity and defects in the active center of the catalyst (such as Fe single atom), thereby affecting the final catalytic performance. In addition, even if the dual anchoring strategy is used, the binding force between Pt nanoparticles and carbon carriers is limited after all, and it is difficult to completely avoid the agglomeration and shedding of Pt particles during long-term use.
[0008] Chinese patent CN 115101766 A prepared a low-platinum cathode oxygen reduction catalyst, in which the MOF precursor may undergo changes in pore structure during carbonization, affecting the transmission of oxygen and protons, thereby affecting the electrochemical performance. The catalyst uses a metal-organic framework (MOF) precursor method, which may cause uneven dispersion of metal particles on the carbon carrier, affecting the catalytic activity.
[0009] China CN 114068969 A prepared a N-doped carbon-based platinum-cobalt alloy oxygen reduction catalyst. Although a certain degree of N doping can be achieved through solvothermal reaction, the controllability of N content and doping form may need to be further optimized. Uneven N doping distribution will cause uneven active centers, thereby affecting the repeatability and stability of catalytic performance. Although the structural scale and morphology of this catalyst can be regulated by synthetic conditions, it is still difficult to achieve precise microstructure design. For example, the fine control of parameters such as alloy particle size, composition ratio, and lattice distortion still faces certain challenges, which may lead to uncertainty in the active sites of the catalyst.
[0010] However, the above-mentioned prior art has the following problems: the bonding strength between Pt nanoparticles and carbon carriers is limited. During long-term use, the activity often decays due to the dissolution, shedding and agglomeration of platinum particles. In addition, since carbon carriers without graphite phases are prone to corrosion, the oxygen reduction performance of the catalyst is greatly reduced, and the stability of such catalysts cannot be guaranteed. The metal Pt particles are unevenly dispersed on the carbon carrier, which affects the catalytic activity. Summary of the invention
[0011] The purpose of the present invention is to address the above-mentioned deficiencies in the prior art and to provide a high-performance iron-nitrogen co-doped carbon-supported platinum catalyst and a preparation method and application thereof.
[0012] The invention discloses an iron-nitrogen co-doped carbon-supported platinum catalyst, comprising a carbon material, the surface of which is doped with iron atoms and nitrogen atoms to form iron-nitrogen-carbon bonds, wherein the iron atoms use nitrogen atoms as nucleation sites to form a large number of uniformly distributed iron atom clusters on the carbon material; platinum nanoparticles use the uniformly distributed iron atom clusters as nucleation sites to grow on the surface of the carbon material, and the platinum nanoparticles obtained by nucleation growth at the iron-nitrogen co-doped sites on the surface of the carbon material are single crystal nanoparticles with strained lattices, and the electron compensation of the platinum nanoparticles by the iron-nitrogen co-doped sites and the lattice strain of the platinum nanoparticles result in higher electrocatalytic activity.
[0013] Furthermore, the particle size of the platinum nanoparticles ranges from 2 to 3 nm.
[0014] A method for preparing an iron-nitrogen co-doped carbon-supported platinum catalyst of the present invention comprises the following steps:
[0015] S1. Prepare a solution of nitrogen source and iron salt, add carbon material, stir, and dry to obtain an iron-nitrogen-carbon mixture;
[0016] S2, sintering the iron-nitrogen-carbon mixture at high temperature to obtain an iron-nitrogen-carbon carrier;
[0017] S3, grinding the iron-nitrogen-carbon carrier and then ultrasonically dispersing it in deionized water;
[0018] S4, adding chloroplatinic acid and potassium chloroplatinate solution and anhydrous formic acid or formaldehyde to the dispersion obtained in step S3, and then ultrasonically dispersing;
[0019] S5, allowing the dispersion obtained in step S4 to stand, removing the supernatant, filtering and drying to obtain the iron-nitrogen co-doped carbon-supported platinum catalyst.
[0020] Furthermore, the iron salt includes one or more of ferric chloride, ferric nitrate and ferric sulfate.
[0021] Furthermore, the nitrogen source includes one or more of urea, melamine and dicyandiamide.
[0022] Furthermore, the carbon material includes one or more of polypyrrole nanowires and graphene oxide.
[0023] Furthermore, the mass ratio of the nitrogen source to the carbon material is 0.5-10:1.
[0024] Furthermore, the mass ratio of the iron source to the carbon material is in the range of 0.2-1:1.
[0025] Furthermore, in the dispersion, the mass ratio of the chloroplatinic acid and potassium chloroplatinate to the iron-nitrogen-carbon carrier is 0.5-0.75:1.
[0026] Furthermore, the high temperature sintering temperature is 800-1000° C., and the sintering time is 1-5 hours.
[0027] Furthermore, in step S5, the standing time is 20-80 hours.
[0028] An iron-nitrogen co-doped carbon-supported platinum catalyst prepared by the above preparation method.
[0029] An application of the iron-nitrogen co-doped carbon-supported platinum catalyst as described above in a hydrogen fuel cell.
[0030] The present invention can form a large number of iron-nitrogen-carbon bonds on the surface of the carbon carrier by simply introducing iron and nitrogen. The formed iron-nitrogen bonds have strong polarity, which can effectively enhance the interaction between platinum and the carbon carrier, provide electron compensation for platinum nanoparticles, and cause lattice strain inside the platinum single crystals formed by their nucleation and growth. This synergistic effect can effectively improve the activity and stability of the catalyst.
[0031] In the present invention, due to the presence of a large number of iron-nitrogen bonds on the surface of the carbon carrier, the nucleation sites of the platinum nanoparticles become abundant, the platinum nanoparticles are more evenly dispersed, and the particle size grown under limited platinum source conditions is smaller, which inhibits the growth of excessively large particles, thereby exposing more active sites and effectively improving the activity of the catalyst. The iron-nitrogen bonds have a strong interaction with the platinum atoms, and the strong interaction of the platinum atoms deposited on the surface of the active sites causes the lattice parameters formed by the initial growth to deviate from the ideal value, resulting in lattice strain, which is retained in the subsequent growth process until the entire particle growth is completed, and the strain is retained in the particles. The intrinsic activity of this highly dispersed, small-sized platinum nanoparticle containing internal strain is greatly improved under the electronic compensation of the iron atoms and nitrogen atoms at the iron-nitrogen bond sites on the surface of the carbon material, effectively improving the activity of the catalyst.
[0032] The present invention firmly anchors platinum atoms through the anchoring of iron-nitrogen bonds, and the nitrogen element can reduce the dissolution rate of platinum, thereby solving the problem of platinum particle ripening.
[0033] The present invention can graphitize the surface of a carbon carrier that does not contain a graphite phase through iron catalytic graphitization. The presence of the iron element improves the graphitization degree of the carbon material, further improves the corrosion resistance of the carbon carrier, solves the problem of carbon carrier corrosion, and plays a role in further improving the stability of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 It is a schematic diagram of the preparation method of the present invention;
[0035] Figure 2 is the XRD pattern of the product prepared in Example 1;
[0036] Figure 3 is a TEM image of the product prepared in Example 1;
[0037] Figure 4is the LSV graph of the products prepared in Examples 1, 4 and Comparative Examples 1, 2, 3;
[0038] Figure 5 is the LSV graph of the products prepared in Comparative Examples 4 to 9;
[0039] Figure 6 This is a performance comparison chart of the product prepared in Example 1 before and after 10,000 ADT cycles;
[0040] Figure 7 This is a performance comparison chart of the product prepared in Example 4 before and after 10,000 ADT cycles;
[0041] Figure 8 This is a performance comparison chart of the product prepared in Example 3 before and after 10,000 ADT cycles. DETAILED DESCRIPTION
[0042] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.
[0043] Example 1
[0044] (1) 3.0 g urea and 0.27 g ferric chloride hexahydrate were dissolved in 40 mL deionized water, 0.5 g polypyrrole nanowires were added and stirred for 2 hours, and then placed in a 60 ° C oven for immersion and drying;
[0045] (2) keeping the mixed solid obtained in step (1) at 900° C. in a tube furnace for 3 hours;
[0046] (3) Grind the solid obtained by sintering in step (2) in a mortar for 20 minutes, then take 30 mg of the ground powder and add it to 40 mL of deionized water, and sonicate it with a 300 W ultrasonic gun for 20 minutes;
[0047] (4) adding 2.0 mL of chloroplatinic acid hexahydrate solution (10 mg / mL) and 3.0 mL of anhydrous formic acid to the dispersion after ultrasonication in step (3), and ultrasonicating in an ultrasonic bath for 30 minutes;
[0048] (5) The dispersion obtained in step (4) was allowed to stand for 72 hours, then filtered and dried to obtain the final product.
[0049] Example 2
[0050] (1) 2.5 g urea and 0.405 g ferric chloride hexahydrate were dissolved in 40 mL deionized water, 0.5 g polypyrrole nanowires were added and stirred for 2 hours, and then placed in an oven at 60 ° C for immersion and drying;
[0051] (2) keeping the mixed solid obtained in step (1) at 800° C. in a tube furnace for 2 hours;
[0052] (3) Grind the solid obtained by sintering in step (2) in a mortar for 20 minutes, then take 30 mg of the ground powder and add it to 40 mL of deionized water, and sonicate it with a 300 W ultrasonic gun for 20 minutes;
[0053] (4) adding 2.0 mL of chloroplatinic acid hexahydrate solution (10 mg / mL) and 3.0 mL of anhydrous formic acid to the dispersion after ultrasonication in step (3), and ultrasonicating in an ultrasonic bath for 30 minutes;
[0054] (5) The dispersion obtained in step (4) was allowed to stand for 48 hours, then filtered and dried to obtain the final product.
[0055] Example 3
[0056] (1) 3.5 g urea and 0.135 g ferric chloride hexahydrate were dissolved in 40 mL deionized water, 0.5 g polypyrrole nanowires were added and stirred for 2 hours, and then placed in a 60 ° C oven for immersion and drying;
[0057] (2) keeping the mixed solid obtained in step (1) at 1000° C. in a tube furnace for 1 hour;
[0058] (3) Grind the solid obtained by sintering in step (2) in a mortar for 20 minutes, then take 30 mg of the ground powder and add it to 40 mL of deionized water, and sonicate it with a 300 W ultrasonic gun for 20 minutes;
[0059] (4) adding 2.0 mL of chloroplatinic acid hexahydrate solution (10 mg / mL) and 3.0 mL of anhydrous formic acid to the dispersion after ultrasonication in step (3), and ultrasonicating in an ultrasonic bath for 30 minutes;
[0060] (5) The dispersion obtained in step (4) was allowed to stand for 24 hours, then filtered and dried to obtain the final product.
[0061] Example 4
[0062] (1) 3.0 g of melamine and 0.40 g of ferric sulfate were dissolved in 40 mL of deionized water, 0.5 g of graphene oxide was added and stirred for 2 hours, and then placed in an oven at 60 ° C for immersion and drying;
[0063] (2) keeping the mixed solid obtained in step (1) at 900° C. in a tube furnace for 3 hours;
[0064] (3) Grind the solid obtained by sintering in step (2) in a mortar for 20 minutes, then take 30 mg of the ground powder and add it to 40 mL of deionized water, and sonicate it with a 300 W ultrasonic gun for 20 minutes;
[0065] (4) adding 2.0 mL of chloroplatinic acid hexahydrate solution (10 mg / mL) and 3.0 mL of anhydrous formic acid to the dispersion after ultrasonication in step (3), and ultrasonicating in an ultrasonic bath for 30 minutes;
[0066] (5) The dispersion obtained in step (4) was allowed to stand for 72 hours, then filtered and dried to obtain the final product.
[0067] Example 5
[0068] (1) 2.5 g of melamine and 0.60 g of ferric sulfate were dissolved in 40 mL of deionized water, 0.5 g of graphene oxide was added and stirred for 2 hours, and then placed in an oven at 60 ° C for immersion and drying;
[0069] (2) keeping the mixed solid obtained in step (1) at 800° C. in a tube furnace for 2 hours;
[0070] (3) Grind the solid obtained by sintering in step (2) in a mortar for 20 minutes, then take 30 mg of the ground powder and add it to 40 mL of deionized water, and sonicate it with a 300 W ultrasonic gun for 20 minutes;
[0071] (4) adding 2.0 mL of chloroplatinic acid hexahydrate solution (10 mg / mL) and 3.0 mL of anhydrous formic acid to the dispersion after ultrasonication in step (3), and ultrasonicating in an ultrasonic bath for 30 minutes;
[0072] (5) The dispersion obtained in step (4) was allowed to stand for 48 hours, then filtered and dried to obtain the final product.
[0073] Example 6
[0074] (1) 4.0 g of melamine and 0.20 g of ferric sulfate were dissolved in 40 mL of deionized water, 0.5 g of graphene oxide was added and stirred for 2 hours, and then placed in an oven at 60 ° C for immersion and drying;
[0075] (2) keeping the mixed solid obtained in step (1) at 1000° C. in a tube furnace for 1 hour;
[0076] (3) Grind the solid obtained by sintering in step (2) in a mortar for 20 minutes, then take 30 mg of the ground powder and add it to 40 mL of deionized water, and sonicate it with a 300 W ultrasonic gun for 20 minutes;
[0077] (4) adding 2.0 mL of chloroplatinic acid hexahydrate solution (10 mg / mL) and 3.0 mL of anhydrous formic acid to the dispersion after ultrasonication in step (3), and ultrasonicating in an ultrasonic bath for 30 minutes;
[0078] (5) The dispersion obtained in step (4) was allowed to stand for 24 hours, then filtered and dried to obtain the final product.
[0079] Comparative Example 1
[0080] A carbon-supported platinum hydrogen fuel cell cathode catalyst was prepared according to the method described in patent CN 117282977A. The specific synthesis method is as follows:
[0081] (1) 69.7 g of sodium citrate and 4.3 g of sodium hydroxide were dissolved in 300 mL of pure water, and 550 mL of methanol was added after the mixture was completely dissolved. The mixture was heated to 40° C. and 67 mL of 0.03 mol / L chloroplatinic acid ethylene glycol solution was added. The reaction solution was heated to 60° C. and placed in a microwave reactor at 800 W for 3 h. The mixture was then cooled and kept at about 15° C.;
[0082] (2) Then, 1000 mL of methanol was added to the mixed solution for the second time. At this time, gray solid powder precipitated from the mixed solution, and the colloid was transformed into a suspension. After being evenly dispersed, 150 mL of 2M H2SO4 was added dropwise. After being kept warm and aged for 8 h, the mixed solution was subjected to solid-liquid separation;
[0083] (3) The obtained solid particles are dried and dissolved in 1000 mL of pure water. After stirring evenly, the color of the mixed solution gradually darkens. After solid-liquid separation, the solid particles are taken out and dried. This step is repeated twice to obtain the desired nano-platinum particles.
[0084] Comparative Example 2
[0085] A carbon-supported platinum hydrogen fuel cell cathode catalyst was prepared according to the method described in patent CN 116581316A. The specific synthesis method is as follows:
[0086] (1) 3.488 g Zn(NO3)2·6H2O and 2.729 g Co(NO3)2·6H2O were dissolved in 75 ml methanol, and then added to 30 ml methanol solution containing 3.08 g 2-methylimidazole prepared in advance, and stirred at room temperature for 24 h. The resulting precipitate was centrifuged, washed with methanol 4 times, and dried at 70 ° C under vacuum for 10 h to obtain ZnCoZIF material;
[0087] (2) The obtained ZnCoZIF was then placed in a ceramic boat and calcined at 950°C for 3 h in a N2 atmosphere. After the temperature dropped to room temperature, a porous nitrogen-doped carbon matrix material rich in Co single atoms (CoSAsZIFNC) was obtained;
[0088] (3) 1000 mg of H2PtCl6 was dissolved in 16.67 mL of deionized water to obtain a 60 mg / mL H2PtCl6 solution, 50 mg of CoSAsZIFNC (Zn / Co = 1.25) was dispersed in 5 mL of H2PtCl6 solution, stirred at 70 °C for 16 h, centrifuged, washed with ethanol three times, and dried at 70 °C for 10 h to obtain a Pt precursor sample;
[0089] (4) The Pt precursor sample was placed in a ceramic boat, placed in a tube furnace, and annealed at 300 °C for 1 h in a H2 / Ar atmosphere. After the temperature dropped to room temperature, a platinum metal nanoparticle catalyst Pt@CoSAs ZIFNC with isolated cobalt single atom sites was finally obtained.
[0090] Comparative Example 3
[0091] The 20% platinum carbon catalyst (Vulkan XC-72 carrier) was purchased from Premetek Corporation of the United States.
[0092] Comparative Example 4
[0093] Except that in step (1), "0.27 g of ferric chloride hexahydrate" was changed to "0.18 g of ferrocene", everything else was the same as in Example 1.
[0094] Comparative Example 5
[0095] Except that the temperature in step (2) is changed from "900°C" to "700°C", everything else is the same as Example 1.
[0096] Comparative Example 6
[0097] Except that "72 hours" in step (5) is changed to "12 hours", everything else is the same as Example 1.
[0098] Comparative Example 7
[0099] The carbon carrier was changed from polypyrrole nanowires to graphene oxide, and the rest was the same as Comparative Example 4.
[0100] Comparative Example 8
[0101] The carbon carrier was changed from polypyrrole nanowires to graphene oxide, and the rest was the same as Comparative Example 5.
[0102] Comparative Example 9
[0103] The carbon carrier was changed from polypyrrole nanowires to graphene oxide, and the rest was the same as Comparative Example 6.
[0104] Table 1
[0105]
[0106] Table 1 lists the electrochemical test results of Examples 1 and 4 and Comparative Examples 1, 2, and 3. It can be seen from the table that the mass activities of Examples 1 and 4 are higher than those of the Comparative Examples. At the same time, Examples 1 and 4 also show good cycle stability.
[0107] Figure 1 It is a schematic diagram of the preparation method of the present invention;
[0108] Figure 2 is the XRD pattern of the product prepared in Example 1; Figure 2 It can be seen that there is a graphite peak at 2Theta = 26°, indicating that the polypyrrole nanowire carrier has been partially graphitized, and the main peak position of the platinum nanoparticles has moved, indicating that its crystal surface has been strained. The average size of the platinum nanoparticles is about 3.0nm, which is consistent with Figure 3 The particle size is highly consistent with that seen in the TEM image.
[0109] Figure 3 is a TEM image of the product prepared in Example 1; Figure 3 It can be seen that the platinum particles are evenly dispersed and the particle size is 2 to 3 nm.
[0110] Figure 4 , Figure 5 is the LSV diagram of the products prepared in Examples 1, 4 and Comparative Examples 1 to 9; Figure 4 and Figure 5 It can be seen that under the same platinum loading, the limiting current and half-wave potential of Example 1 are both the highest, which means that the performance of Example 1 is the best. This is mainly because in Comparative Example 4, ferrocene is volatile and cannot form sufficient Fe-N bonds with the carrier, in Comparative Example 5, the temperature is not high enough to form sufficient Fe-N bonds, and in Comparative Example 6, the time is too short to fully reduce platinum ions, which is not conducive to the growth of platinum particles.
[0111] Figure 6 This is a performance comparison chart of the product prepared in Example 1 before and after 10,000 ADT cycles; Figure 7 This is a performance comparison chart of the product prepared in Example 4 before and after 10,000 ADT cycles; Figure 5 This is a performance comparison chart of the product prepared in Example 3 before and after 10,000 ADT cycles. Figure 6-Figure 8 It can be seen that compared with the product prepared in Example 1 and Comparative Example 3, i.e., commercial platinum carbon, Examples 1 and 4 exhibited good cycle stability.
[0112] For matters not mentioned above, the prior art applies.
[0113] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the present invention.
Claims
1. An iron-nitrogen co-doped carbon-supported platinum catalyst, characterized in that: The invention comprises a carbon material, the surface of which is doped with iron atoms and nitrogen atoms to form iron-nitrogen-carbon bonds, wherein the iron atoms use nitrogen atoms as nucleation sites to form a large number of uniformly distributed iron atom clusters on the carbon material; and platinum nanoparticles use the uniformly distributed iron atom clusters as nucleation sites to grow on the surface of the carbon material.
2. The iron-nitrogen co-doped carbon-supported platinum catalyst according to claim 1, characterized in that: The particle size of the platinum nanoparticles is in the range of 2 to 3 nm; the platinum nanoparticles are single crystal nanoparticles with strained lattices.
3. The method for preparing an iron-nitrogen co-doped carbon-supported platinum catalyst according to claim 1 or 2, characterized in that: The steps include: S1. Prepare a solution of nitrogen source and iron salt, add carbon material, stir, and dry to obtain an iron-nitrogen-carbon mixture; S2, sintering the iron-nitrogen-carbon mixture at high temperature to obtain an iron-nitrogen-carbon carrier; S3, taking a certain amount of the ground iron-nitrogen-carbon carrier and ultrasonically dispersing it in deionized water; S4, adding chloroplatinic acid or potassium chloroplatinate solution and anhydrous formic acid or formaldehyde to the dispersion obtained in step S3, and then ultrasonically dispersing; S5, allowing the dispersion obtained in step S4 to stand, removing the supernatant, filtering and drying to obtain the iron-nitrogen co-doped carbon-supported platinum catalyst.
4. The preparation method according to claim 3, characterized in that: The iron salt includes one or more of ferric chloride, ferric nitrate and ferric sulfate; the nitrogen source includes one or more of urea, melamine and dicyandiamide.
5. The preparation method according to claim 1, characterized in that: The carbon material includes one or more of polypyrrole nanowires and graphene oxide.
6. The preparation method according to claim 1, characterized in that: The mass ratio of the nitrogen source to the carbon material is 0.5-10:1; the mass ratio of the iron source to the carbon material is in the range of 0.2-1:
1.
7. The preparation method according to claim 1, characterized in that: In the dispersion, the mass ratio of the chloroplatinic acid and potassium chloroplatinate to the iron-nitrogen-carbon carrier is 0.5-0.75:
1.
8. The preparation method according to claim 1, characterized in that: The high temperature sintering temperature is 800-1000°C and the sintering time is 1-5 hours.
9. The preparation method according to claim 1, characterized in that: In step S5, the standing time is 20-80 hours.
10. Use of the iron-nitrogen co-doped carbon-supported platinum catalyst as claimed in claim 1 or 2 in a hydrogen fuel cell.
